Legal Consequences and Legal Protection of Notarial Deeds Made Based on False Circular Document - Jihan Fernanda; Istislam Istislam; R. Imam Rahmat Sjafi’i (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Actual or potential, within the limits of reasonable expectation, a Notary may make an authentic deed, but it turns out that the circular document used as the basis for making the authentic deed turns out to be fake. Therefore, this research aims to analyze the consequences and legal protection of Notarial deeds made based on fake circular documents. This research is a normative research that uses statute and conceptual approach. The conclusion of this research is the legal consequences of a Notarial deed made based on a fake circular document, then the party who feels aggrieved by the validity of the deed can apply for the cancellation of the deed to the Court and the Notary is not liability and accountability for the deed he made. Such legal consequences can also be seen as legal protection for Notaries who make deeds but the deeds are based on fake circular documents presented by the parties, so that Notaries are exempted from liability and accountability as long as Notaries have carried out their profession in accordance with applicable protocols and codes ethics